2009
DOI: 10.1002/prot.22219
|View full text |Cite
|
Sign up to set email alerts
|

Residue‐wise conformational stability of DLC8 dimer from native‐state hydrogen exchange

Abstract: Dynein light chain (DLC8) is the smallest subunit of the dynein motor complex, which is known to act as a cargo adaptor in intracellular trafficking. The protein exists as a pure dimer at physiological pH and a completely folded monomer below pH 4. Here, we have determined the energy landscape of the dimeric protein using a combination of optical techniques and native-state hydrogen exchange of amide groups, the former giving the global features and the latter yielding the residue level details. The data indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Further, between the two helices, the stability index suggests that the α2-helix is more stable than the α1-helix. The higher stability of the α2-helix, β4 and β5 sheets compared with those of the remaining structural elements is consistent with the presence of some residues in there whose peaks did not lose intensity even after 4 months in the NHX experiment (Mohan et al 2009a).…”
Section: Stability Of the Native State: Dissection At Residue Levelsupporting
confidence: 64%
See 3 more Smart Citations
“…Further, between the two helices, the stability index suggests that the α2-helix is more stable than the α1-helix. The higher stability of the α2-helix, β4 and β5 sheets compared with those of the remaining structural elements is consistent with the presence of some residues in there whose peaks did not lose intensity even after 4 months in the NHX experiment (Mohan et al 2009a).…”
Section: Stability Of the Native State: Dissection At Residue Levelsupporting
confidence: 64%
“…One more noticeable feature is the increase in unfolding free energy (ΔG uf ) values, i.e. upward slope (m-value) with an increase in the GdnHCl concentration for the residues T26 and Q27 in the α1-helix, suggesting a different type of stability in this segment (Brorsson et al 2006;Mohan et al 2009a) (fi gure 7C right panel). In the case of β-strands, both local and global mechanisms do exist.…”
Section: Stability Of the Native State: Dissection At Residue Levelmentioning
confidence: 97%
See 2 more Smart Citations
“…It is evident that Ser 88 in WT dimer does show a curved temperature dependence of amide proton chemical shifts. Thus, it can be concluded that the amide proton in Ser 88 in WT DLC8 dimer is transiently H-bonded; that it is not a stable H-bond was independently inferred from deuterium exchange studies Mohan et al 2008a). Moreover, the dimeric structure suggests that the amide group of Gly 89 is very close (~ 2.6 Ǻ) to the backbone nitrogen of Ser 88 suggesting a possibility of potential transient H-bonding.…”
Section: Conformational Fluctuations At the Phosphorylation Site Of Dmentioning
confidence: 96%